Stochastic simulation based reliability analysis with multiple performance objective functions - Bansal, Sahil (2015)
In this paper, we propose a stochastic simulation approach to estimate the failure probability of multiple performance objectives as a function of various combinations of thresholds, each threshold corresponding to one performance objective. The proposed approach is robust with respect to the dimension of the failure probability integral, model complexity and nonlinearity. The effectiveness and efficiency of the proposed method are illustrated by a numerical example involving a structural dynamic system subjected to future earthquake excitations modeled as a stochastic process and the results are compared to those obtained using crude Monte Carlo simulation.